GEOMORPHOLOGY AND SEDIMENTOLOGICAL PROCESSES ALONG THE COASTAL ZONE BETWEEN LIVANATES AND AGIOS KONSTANTINOS (N. EVOIKOS GULF, CENTRAL GREECE) - Tsanakas, K.; Gaki-Papanastassiou, K.; Poulos, S.E.; Maroukian, H. (Bulletin of the Geological Society of Greece, 2010)
This study deals with aspects of geomorphology and nearshore marine processes in the coastal zone located between Livanates and Agios Konstantinos (North Evoikos Gulf, central Greece). Evoikos Gulf is a tectonic graben bounded by WNW-ESE trending normal faults; it can be further characterized as semi-closed marine basin with water depths exceeding 400m.The Coastal geomorphology is affected by active tectonics with the most prominent morphological features being the uplifted marine terraces and the well-developed deltaic fan of Xerias torrent. In the present investigation, detailed geomorphological mapping at a scale of 1:5000 was performed together with granulometric analysis, while nearshore wave and current activity related to sediment dynamics has been determined on the basis of wind-generated wave regime. The examined coastal zone consists of a series of alluvial cones and fans, Xerias fan being the largest among them, low cliffs, a cuspate foreland and beach zones of limited length, often hosting beachrock formations. The formation and evolution of the study area seems to be controlled by the limited terrestrial influxes, the relatively weak wave regime due to limited wave fetches distances, and the associated longshore currents that induces limited sediment transport.